Analysis Of Calligraphy Skills of College Students Department Of Arabic Language Education Faculty Of Tarbiyah and Teacher Science North Sumatra State Islamic University - Hamidah Hartono; Haidarul Gholib Al Ghozi (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
Learning calligraphy is an implementation of ability and potential and proficiency in writing Arabic. However, calligraphy writing does not only write about the art of beauty in Arabic, but there are other views, namely cognitive, affective and psychomotor. This study aims to describe the abilities and skills of students in writing calligraphy as well as the correct rules in writing Arabic khat. This research is a qualitative descriptive study. The subjects of this study were students of the North Sumatra State Islamic University (UINSU) Arabic language education-1 (stamp 2022), while the object of this research was in the form of material objects and objects from the results of their studies. The research focused on problems related to the level of difficulty and ease of writing Arabic khat (calligraphy). This data was obtained by means of structured interviews, namely literature studies and research documentation. Then the results of this study are: calligraphy writing in a psychomotor way, which means students' skills in writing calligraphy and calligraphy writing in a cognitive way is related to student intelligence and calligraphy writing ideas are based on affective, namely emotional, character and morals.